Illness Cognitions in ALS: New Insights Into Clinical Management of Behavioural Symptoms - Caga, Jashelle; Devenney, Emma; Huynh, William; Zoing, Margaret C.; Ahmed, Rebekah M.; Kiernan, Matthew C. (Frontiers in Neurology, 2021)
Timely management of frontotemporal dysfunction associated with amyotrophic lateral sclerosis (ALS) has important prognostic and therapeutic implications. However, there remains a paucity of research on best practise recommendations to guide the development of interventions for cognitive and behavioural symptoms as part of ALS care. Accordingly, a focus on illness perceptions may provide a preliminary framework for managing cognitive and behavioural symptoms. The aim of the present study was to explore the nature of illness perceptions among ALS patients with cognitive and behavioural symptoms. A total of 39 patients were recruited from a specialised ALS clinic. Factor analysis showed three independent and clinically interpretable factors corresponding to “cognitive and emotion related ALS perceptions,” “cognitive- specific ALS perceptions” and “ALS coherence”. Of these factors, greater perceived cognitive and emotional impacts of ALS were associated with an approximate 4-fold increased risk of behavioural changes (p < 0.05). Greater perceived cognitive and emotional impacts of ALS was also associated with more rapid disease progression (p < 0.001). As such, timely provision of intervention addressing perceptions about the impact of ALS on functioning as well as associated emotional distress may optimise clinical management of cognitive and behavioural symptoms of ALS.